2010
DOI: 10.1055/s-0030-1267381
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Massive Allograft with Intramedullary Fibular Graft for Intercalary Reconstruction after Resection of Tibial Malignancy

Abstract: Reconstruction after intercalary excision of tibia malignancy is challenging. The combined use of a vascularized fibular flap and allograft can provide a reliable reconstructive option. Eight patients underwent reconstruction with an allograft and vascularized fibula following tibia malignancy resection. Patients were examined clinically and radiographically. The average age of patients was 16.5 years. The mean follow-up time was 38.4 months. Contralateral free fibula flap was used in three patients and ipsila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…After tumor removal, massive allograft in combination with an ipsilateral transferred pedicled fibular graft was used for reconstruction (Fig. 5), which was described in a previous study [18].…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…After tumor removal, massive allograft in combination with an ipsilateral transferred pedicled fibular graft was used for reconstruction (Fig. 5), which was described in a previous study [18].…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Allograft fracture is a recognized complication that occurs after the use of massive bone allografts in up to 20% of patients [5,8,30,35,36,40]. Because the free fibular grafts provide an intrinsic blood supply, bony union can occur through the process similar to normal fracture healing [14,16,24,38,42]. Although fractures were common in our series, the intramedullary free fibula allowed the fractures to heal with ORIF or nonoperatively, which could not occur in an allograft alone.…”
Section: Discussionmentioning
confidence: 88%
“…Current options for limb salvage surgery include large cortical allografts, endoprostheses, distraction osteogenesis, and vascularized fibular graft [3,9,20,24,34,35]. Massive structural allografts have been most frequently used for limb reconstruction; however, complications such as allograft infection and fracture are common as a result of the avascular nature of the graft [24]. The Capanna technique was developed to add biology to the avascular graft to help reduce these complications [12]; however, reports of the use of the Capanna technique in the pediatric and adolescent populations are limited [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-vascularized bone auto-graft and allograft are adopted to reconstruct defects less than 5cm while vascularized fibular grafts are the most common treatment for necrotic tibial defects greater than 5cm(Brigman et al The grafting fibula was constantly thickening with new bone creeping along it -the thickening parts were cortical bone, the tibial defects were finally replaced by grafting fibula (Chen et al, 2014; Tanaka et al, 2012). However, the grafting fibula would not grow indefinitely and the maximum value of the diameter was no more than the tibia (Li et al 2011). The grafting fibula grew slowly for the patients more than 18 years old and we concluded that age was an important factor influencing the growth of grafting fibula.…”
Section: Discussionmentioning
confidence: 99%